Estimated total amyloid burden from 18F-florbetaben positron emission tomography predicts all-cause mortality in light-chain cardiac amyloidosis - Vergaro, Giuseppe; Aimo, Alberto; Genovesi, Dario; Bezerra, Lucas Soares; Castiglione, Vincenzo; Fabiani, Iacopo; Barison, Andrea; Panichella, Giorgia; Del Giudice, Maria Livia; Camerini, Lara; Dugo, Giovanni; Chubuchna, Olena; et al. (European heart journal - cardiovascular imaging, 2025)
The positron emission tomography (PET) tracer 18F-florbetaben is a promising diagnostic tool for light-chain cardiac amyloidosis (AL-CA). A greater cardiac uptake might signal more amyloid burden and a worse outcome. We aimed to assess the prognostic significance of 18F-florbetaben uptake in AL-CA.Consecutive patients with AL-CA underwent 18F-florbetaben PET scans. Total amyloid burden (TAB; calculated as mean standardized uptake value multiplied by molecular volume) was assessed in the left and right ventricles (LV/RV) in early (5-15′) and late (50-60′) acquisitions. The endpoint was all-cause mortality. Forty patients (median age 69 years, 73% males, Mayo 2004 Stage III in 80%) underwent 18F-florbetaben PET with a median time from tissue biopsy of 21 days (interquartile range, IQR 7-83). Late LV TAB, but not early LV TAB, correlated with N-terminal pro-B-type natriuretic peptide (NT-proBNP) and high-sensitivity (hs)-troponin T. Over 13 months after the PET scan (IQR 5-21), 65% of patients died. A late LV TAB ≥273 cm3 (cut-off derived from spline curve analysis) predicted 18 and 24 month all-cause mortality independently from baseline variables, including NT-proBNP, hs-troponin T, and Mayo 2004 stage. Late RV TAB ≥135 cm3 independently predicted 18 and 24 month all-cause mortality. Patients with both late LV and RV TAB ≥ cut-offs had a shorter survival than those with only LV TAB ≥ cut-off and those with TAB in both ventricles < cut-offs (Log-rank 16.52, P < 0.001).18F-florbetaben PET imaging offers valuable prognostic information in AL-CA. Values of late TAB measured in the LV and RV are strong predictors of all-cause mortality.
Online veröffentlicht: 23. Dezember 2024
Im Titel ist die Zahl 18 hochgestellt
Gesehen am 07.08.2025